Korelasi Antara Penerapan Pestisida Serta Panen Sering, Pemangkasan, Sanitasi, Pemupukan (Pspsp) Terhadap Hasil Dan Pendapatan Petani Perkebunan Rakyat Kakao Aceh Tenggara - Ramut, Anuar (AGROSUSTAIN, 2025)
Southeast Aceh is one of the regencies in Aceh Province with high potential in the agricultural sector. Most of the population are cocoa farmers. However, the potential yield is often lost due to a lack of attention to proper cocoa cultivation techniques, including frequent harvesting, fertilization patterns and dosages, sanitation, pruning, and the use of herbicides, insecticides, and fungicides. This study aims to examine the cultivation techniques used by smallholder cocoa farmers in Southeast Aceh Regency. The research was conducted in May 2025 across 12 subdistricts in Southeast Aceh Regency, Aceh Province. This study employs an ex post facto design through field research. The tools and materials used included a questionnaire (Appendix 1). Data were collected through interviews and subsequently analyzed using quantitative and qualitative descriptive methods. The results showed that the average education level of cocoa farmers in Southeast Aceh is high school. The average land area was 6,930.32 m². Sanitation was carried out 3.28 times per year, light pruning 4.43 times per year, and heavy pruning 1.50 times per year. Fertilizer dosages were 160.13 kg/year for urea, 105.02 kg/year for TSP, 91.13 kg/year for KCl, and 126.94 kg/year for manure. Herbicide usage was 2.30 liters/year, insecticides 1.11 liters/year, and fungicides 0.86 liters/year. Harvesting was conducted every 10.54 days, yielding 47.26 kg per frequent harvest, 1.23 tons annually, with an annual revenue of IDR 123,171,759.26, expenditures of IDR 14,642,949.07, and a net profit of IDR 108,528,810.19 per year. Further experimental research is needed on cocoa cultivation techniques—specifically on the application of frequent harvesting, pruning, sanitation, and fertilization—to improve the growth and yield of cocoa plants.